Designing a Vanilla Sales Application System using Fremwork Service Oriented Architecture (SOA) - Sudin Saepudin; Hihin Nurhayati; Falentino Sembiring (Jurnal Mantik, 2022)
CV. Vanilla Gemstone is one of the leading vanilla ditributor conpanies in Sukabumi. The preparation of a comprehensive business plan is based on a sales strategy. While at this time the management of sales at CV. Vanilla Gemstone is still less effective because CV. Vanilla Gemstone during the sale, the owner places order or sales via telephone or short massage so that an efficient way for the sales segment has not been found. Then the so called old fashioned way in the sales system itself, resulting in sales figures that are not increasing day by day. It can make the company will experience defeat in business comprtition by other trading rivals. Based on these problems, we need an application that can manage vanilla sales more effeciently.